Love Stories: How Language Use Patterns Vary by Relationship Quality. Issue 1 (2nd January 2020) - Robinson, Michael D.; Persich, Michelle R.; Sjoblom-Schmidt, Simona; Penzel, Ian B.
ABSTRACT: Romantic relationships vary in quality, and the purpose of the present investigation was to examine a wide scope of linguistic variables as possible markers of this variability. Ninety-six undergraduate students within committed romantic relationships were asked to write freely about their partnership, following which they reported on relationship qualities such as trust, love, and satisfaction. In addition, 87 partners reported on their perceptions of relationship closeness, and 88 participants completed at least 8 days of a daily diary protocol. The occurrence of positive emotion words predicted relationship satisfaction, and the use of first-person plural words predicted partner perceptions of closeness. Beyond such findings, relationship quality varied positively with linguistic certainty, inclusiveness, and expressiveness. Conversely, several findings point to linguistic variables, such as anxiety, that suggest inhibitory processes within the relationship. Altogether, the research extends our knowledge concerning the linguistic factors that differentiate high-quality relationships from less functional ones.